PENERAPAN PRINSIP BAGI HASIL PADA PEMBIAYAAN DI BANK SYARIAH MENURUT UNDANG-UNDANG PERBANKAN SYARIAH - Wulandari, Andi Sri Rezky; Basir, Abd. (Fakultas Syariah Institut Agama Islam Negeri (IAIN) Pontianak, 2020)
Ratification of RI Law No. 21 of 2008 concerning Sharia Banking is one of the legal instruments for the growth of the Islamic banking industry in Indonesia. The main principle applied is the principle of profit-sharing with quite basic character differences from the interest system, one of them is financing product. Even so in practice, the composition of Islamic finance with the principle of profit-sharing is still far from expected. Therefore, this study examines the application of profit-sharing principles to Islamic finance according to RI Law No. 21 of 2008. The results of this study found that sharia financing with the principle of profit-sharing in the form of mudharabah and musyarakah are following the law. In the profit-sharing scheme, it not only divides the profits as stated in the contract but also the losses that correspond to capital.